Rorty: uma utopia de primazia da literatura e da liberdade - Araújo de Sousa, Vigevando,Carvalho Marques, Wilker de (SSOAR, GESIS – Leibniz-Institut für Sozialwissenschaften e.V., 2022)
Abstract: Richard Rorty (1931-2007) stood out as a relevant thinker of contemporary political life, in addition to building a framework of ideas of language, culture, freedom and solidarity. One of his most recurrent banners was the primacy of literature over philosophy and freedom over truth. For the purposes of this article, we start with excerpts from Rorty's interview by Helmut Mayer and Wolfgang Ulrich, compiled in the text It's good to persuade, in Take care of freedom that the truth will take care of itself. In addition to this text, we also use Philosophy and social hope (from 1999), and, in particular, Education as socialization and individualization (from 1989), a text in which the author, moving away from the enchantment of traditional philosophy and defending the adoption of a philosophizing, primacy of freedom the edifying truth, by dogmatic, over a markedly essentialist and anti-foundationist posture
10.31977/grirfi.v22i2.2826
Keywords: (thesoz)Rorty; R.; (thesoz)Utopie; (thesoz)Freiheit; (thesoz)Wahrheit; (thesoz)Literatur